A TSV-Based Helical Dual-Band Antenna. Issue 1 (1st January 2023) - Wang, Fengjuan; Ren, Jiashuo; Yu, Ningmei; Yang, Yuan
Abstract: This paper come up with a novel helical dual-band antenna that can be used in terahertz (THz) band applications. The antenna is fed by a redistribution layer (RDL), and the metal patch is formed on the top and bottom surfaces of the silicon dielectric substrate, which is connected by through-silicon via (TSV) to form a helical structure. At the same time, better impedance matching can be achieved by changing the shape of the ground plate to achieve dual-band characteristics. The simulation results presentation that the return loss of the antenna in 319GHz-339GHz and 373GHz-388GHz is less than -10db, and it has good axial radiation characteristics.